Measuring Market Expectations - Christiane Baumeister (Center for Economic Studies and ifo Institute (CESifo), 2021)
Asset prices are a valuable source of information about financial market participants.expectations about key macroeconomic variables. However, the presence of time-varying risk premia requires an adjustment of market prices to obtain the market's rational assessment of future price and policy developments. This paper reviews empirical approaches for recovering market-based expectations. It starts by laying out the two canonical modeling frameworks that form the backbone for estimating risk premia and highlights the proliferation of risk pricing factors that result in a wide range of different asset-price-based expectation measures. It then describes a key methodological innovation to evaluate the empirical plausibility of risk premium estimates and to identify the most accurate market-based expectation measure. The usefulness of this general approach is illustrated for price expectations in the global oil market. Then, the paper provides an overview of the body of empirical evidence for monetary policy and inflation expectations with a special emphasis on market-specific characteristics that complicate the quest for the best possible market-based expectation measure. Finally, it discusses a number of economic applications where market expectations play a key role for evaluating economic models, guiding policy analysis, and deriving shock measures.
Keywords: C52; E31; E43; E52; G14; Q43; 330; futures markets; risk premia; monetary policy; commodities; market expectations; financial markets; asset pricing; return regressions; affine term structure models; risk adjustment; model uncertainty; forecasting; expectational shocks